Chromosomal translocation t(11;18)(q21;q21) in gastrointestinal mucosa associated lymphoid tissue lymphoma. Issue 1 (1st January 2003) - Nakamura, S; Matsumoto, T; Nakamura, S; Jo, Y; Fujisawa, K; Suekane, H; Yao, T; Tsuneyoshi, M; Iida, M
Abstract : Aims: To evaluate the chromosomal translocation t(11;18)(q21;q21) in gastrointestinal lymphomas. Methods: A possible API2–MLT fusion transcript specific to t(11;18)(q21;q21) was examined by means of reverse transcription-polymerase chain reaction (RT-PCR) in tumours from 47 cases of primary gastrointestinal lymphoma (28 low grade mucosa associated lymphoid tissue (MALT) lymphomas, four low grade MALT lymphomas with a high grade component, nine secondary diffuse large B cell lymphomas, four primary diffuse large B cell lymphomas, and two T cell lymphomas). Results: API2–MLT fusion was seen in four of 28 cases of low grade MALT lymphoma, but it was not seen in other types of lymphoma. Among the low grade MALT lymphomas, the fusion transcript was seen more frequently in colonic tumours than in gastric tumours (two of three compared with two of 24) and in tumours with submucosal invasion than in those confined to the mucosa (four of 13 compared with 0 of 15). Helicobacter pylori negative tumours tended to show a higher positive rate than H pylori positive tumours (three of six compared with one of 21). None of the gastric tumours that responded to H pylori eradication expressed the API2–MLT fusion transcript. Conclusions: t(11;18)(q21;q21) seems to be one of the genetic alterations related to the development of gastrointestinal low grade MALT lymphoma. Such translocations may be predominantly associated with the development of intestinal MALT lymphoma.